Developing data analytics capabilities of circular economy SMEs - Järvenpää, Anne-Mari (Vaasan yliopisto, 2022)
The sustainability crisis demands action to match consumption and production to the limits of the nature. The circular economy is expected to solve the sustainability challenge, in which the recycling and waste management industry are envisioned to play a major role maintaining materials in a cycle to reduce the need for virgin materials. There are high expectations that digitalization and increasing amounts of data will provide the keys to develop efficient circular material cycles. Thus, it is relevant to ask how companies operating in the circular economy, especially SMEs, are able to utilize this data. This dissertation integrates the circular economy, data-driven decision-making and data analytics capabilities, and seeks answers to the research question: What kinds of capabilities, needs and challenges do SMEs in the circular economy have for data utilization, and how these capabilities could be improved by means of collaboration with universities? This question is divided into four sub-questions, which are addressed in four research articles. The research was conducted as a qualitative case study by collecting empirical data from seven case companies that operate in the field of the circular economy—namely in recycling and waste management. This research was conducted during 2018–2022 in Finland. The results of this study increase the understanding of how circular economy SMEs utilize data in decision-making, what their practical challenges are regarding data utilization, and how SMEs in the circular economy could improve their data utilization capabilities. The results reveal that the data utilization needs for SMEs in the circular economy relate to planning operations and preparing for the future in terms of increasing competition, changing trends, high environmental standards, investing in facilities and capabilities and reducing carbon emissions. The challenge is to combine relevant data from several internal and external sources and use analytics. These challenges relate to data management, lack of resources and capabilities, as well as to regulation. Moreover, circular economy SMEs are more driven by regulation than by data.

Kestävyyskriisi vaatii toimia, joilla kulutus ja tuotanto sovitetaan luonnon kantokykyyn. Kiertotalouden odotetaan ratkaisevan kestävyyshaasteen, jossa kierrätys- ja jätehuoltoteollisuudella on suuri rooli materiaalien kierrossa ja neitseellisen materiaalitarpeen vähentämisessä. Digitalisaatio ja datan kasvava määrä tarjoavat avaimet tehokkaiden materiaalikiertojen kehittämiseen. Siksi on olennaista kysyä, miten kiertotaloudessa toimivat yritykset, erityisesti pk-yritykset, pystyvät hyödyntämään dataa. Tämä väitöskirja yhdistää kiertotalouden, dataan pohjautuvan päätöksenteon ja data-analytiikan kyvykkyydet hakien vastausta tutkimuskysymykseen: Millaisia kyvykkyyksiä, tarpeita ja haasteita kiertotalouden pk-yrityksillä on datan hyödyntämiseen ja miten kyvykkyyksiä voitaisiin parantaa yhteistyössä korkeakoulujen kanssa? Tämä kysymys on jaettu neljään alakysymykseen, joita käsitellään neljässä tutkimusartikkelissa. Tutkimus toteutettiin laadullisena tapaustutkimuksena keräämällä empiiristä dataa seitsemästä pk-yrityksestä, jotka toimivat kiertotalouden alalla, tarkemmin kierrätyksen ja jätehuollon parissa. Tutkimus toteutettiin vuosina 2018–2022 Suomessa. Tämän tutkimuksen tulokset lisäävät ymmärrystä siitä, miten kiertotalouden pk-yritykset hyödyntävät dataa päätöksenteossa, mitkä ovat niiden käytännön haasteet datan hyödyntämisessä ja miten pk-yritykset voisivat parantaa kykyään hyödyntää dataa. Tulokset paljastavat, että kiertotalouden pk-yritysten datan hyödyntämistarpeet liittyvät toiminnan suunnitteluun ja tulevaisuuteen varautumiseen kilpailun lisääntyessä, muuttuviin trendeihin, kasvaviin ympäristövaatimuksiin, investointeihin sekä hiilidioksidipäästöjen vähentämiseen. Haasteena on yhdistää relevanttia dataa useista sisäisistä ja ulkoisista lähteistä sekä käyttää analytiikkaa. Nämä haasteet liittyvät tiedonhallintaan, resurssien ja kyvykkyyksien puutteeseen sekä sääntelyyn. Lisäksi kiertotalouden pk-yrityksiä näyttää ohjaavan enemmän sääntely kuin data.
Keywords: circular economy; sustainable development; innovations; leadership (activity); small and medium-sized enterprises; recycling; green economy; waste management; universities; universities of applied sciences; fi=Tuotantotalous|en=Industrial Management|